2023
DOI: 10.3389/fpls.2023.1150198
|View full text |Cite
|
Sign up to set email alerts
|

Calcium dynamics and modulation in carrot somatic embryogenesis

Abstract: Free calcium (Ca2+) is a pivotal player in different in vivo and in vitro morphogenic processes. In the induction of somatic embryogenesis, its role has been demonstrated in different species. In carrot, however, this role has been more controversial. In this work, we developed carrot lines expressing cameleon Ca2+ sensors. With them, Ca2+ levels and distribution in the different embryogenic structures formed during the induction and development of somatic embryos were analyzed by FRET. We also used different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Ca 2+ is known to induce and regulate the expression of CAM and CAM‐like proteins that are players in Ca 2+ ‐mediated signal transduction (Anil & Rao, 2000). The efficiency of SE in plants can be effectively modulated by allowing, within a range, additional Ca 2+ to enter the cell to act as a second messenger to trigger embryogenesis induction (Anil & Rao, 2000; Calabuig‐Serna et al ., 2023). It has been reported that Ca 2+ levels increased in the cells of the regions where somatic embryos will be formed, thereby constituting early markers of the embryogenic regions (Denninger et al ., 2014; Calabuig‐Serna et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ca 2+ is known to induce and regulate the expression of CAM and CAM‐like proteins that are players in Ca 2+ ‐mediated signal transduction (Anil & Rao, 2000). The efficiency of SE in plants can be effectively modulated by allowing, within a range, additional Ca 2+ to enter the cell to act as a second messenger to trigger embryogenesis induction (Anil & Rao, 2000; Calabuig‐Serna et al ., 2023). It has been reported that Ca 2+ levels increased in the cells of the regions where somatic embryos will be formed, thereby constituting early markers of the embryogenic regions (Denninger et al ., 2014; Calabuig‐Serna et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of SE in plants can be effectively modulated by allowing, within a range, additional Ca 2+ to enter the cell to act as a second messenger to trigger embryogenesis induction (Anil & Rao, 2000; Calabuig‐Serna et al ., 2023). It has been reported that Ca 2+ levels increased in the cells of the regions where somatic embryos will be formed, thereby constituting early markers of the embryogenic regions (Denninger et al ., 2014; Calabuig‐Serna et al ., 2023). Meanwhile, altering Ca 2+ signaling by reducing their levels or interfering with CAM has a significantly negative impact on embryogenesis induction (Calabuig‐Serna et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most studies have investigated the mechanisms of SE process induction using model plant species such as Arabidopsis thaliana [ 15 ], carrot [ 16 ], alfalfa [ 17 ], maize [ 18 ] and rice [ 19 ]. Lilies are monocotyledons of the Liliaceae and are the most important bulb crops [ 20 ].…”
Section: Introductionmentioning
confidence: 99%